Divorced wife’s right to maintenance under Islamic and civil law: possibility of harmonisation - Mohd, Azizah; Abd Malek, Normi; Hj Ibrahim, Badruddin; Mohd Najid, Khadijah (Harun M Hashim Law Centre, IIUM, 2023)
Relationship between husband and wife creates certain rights and obligations that both are to enjoy and fulfil especially during the subsistence of marital relationship. Both Islamic and civil law agree that maintenance is one of the rights of the wife and one of the obligations of the husband. The right continues even after the wife is divorced but subject to certain conditions and limitations under which the two laws differ. This paper seeks to examine especially the point of differences on the divorced wife’s right to maintenance under both the Islamic and civil law. The paper aims to critically investigate whether the civil law on right of divorced wife to maintenance may be harmonised with the Islamic law. For that purpose, the discussion will include the provisions of divorced wife’s rights to maintenance under Islamic law (the Shari’ah) as well as the provisions of the law that governs the Muslims in Malaysia. The discussion will extend to several other means to protect the financial rights of divorced wife in Islam such as consolatory gift (mut’ah) and recovery of arrears of maintenance. As regards to civil law, the paper will highlight several provisions of civil law that governs the non-Muslims particularly the Married Women and Children (Maintenance) Act (1950) and the Law Reform (Marriage and Divorce) Act 1976. This research adopts a qualitative methodology whereby analysis will be made based on materials in library and statutes. Finally, this paper will provide suggestions on harmonisation of Islamic and Civil law where relevant and possible.